A prospective study of injuries in elite soccer referees and assistant referees. Issue 4 (27th March 2011) - Wilson, F; Gissane, C; Byrne, A
Abstract : Background: Injury incidence in soccer players has received wide attention, but there is a lack of information dealing with match officials. Objective: To examine the profile and incidence of injury in soccer match officials. Design: A 12 month prospective cohort injury surveillance programme. Setting: Elite soccer referees and assistant referees who were part of the Football Association of Ireland referee database. Participants: 31 participants (27 males and 4 females), mean age 33.2 (6.2) years old (69% of the available cohort). Assessment of risk factors: Weekly web based survey, followed up by a telephone interview in those cases who reported injury. Main outcome measurements: Details of training and match officiating. New injuries in terms of site of the body, type of injury, where, when and how it took place. Results: Most activity time was spent training (61%) with 39% spent officiating. 38 injuries were recorded, (8.8/1000 h training (CI 6.2 to 12.0) and 16.4/1000 h for match officiating (CI 10.9 to 23.8), (RR 4.3, 2.1 to 8.9)). 55% (CI 40 to 70%) were injuries to muscles. 76% (CI 61 to 87) were to the lower leg. Overuse injuries represented 61% (CI 45 to 74%) of all cases. Achilles tendinopathy and hip/groin muscle strain were the most common injuries (18.4% of all injuries each). The proportion of overuse injuries that took place in matches (68%) and training (40%) were not significantly different (difference=28%, 95% CI −6 to 55). Only two injuries (5.3%, 95% CI 1.5 to 17.0) involved contact, both during training. Conclusion: Elite match officials complete high volumes of training and officiating. Match officials are at risk of sustaining injury which in training, is similar to the incidence reported in soccer players.